Sharing the Fame but Taking the Blame: When Declaring a Single Person Responsible Solves a Free Rider Problem - Xinyu Li; Wendelin Schnedler (Institute of Labor Economics (IZA), 2024)
Teams are formed because input from different people is needed. Providing incentives to team members, however, can be diffcult. According to received wisdom, declaring all members responsible fails because real responsibility for team output 'diffuses'. But why? And why and when does formally declaring one member 'responsible' mean that this member can be attributed real responsibility? We offer a model that answers these questions. We identify when jointly declaring a team responsible results in reputation free-riding. We show that declaring one person responsible can overcome this problem but only if all other team members are protected from being sanctioned.
Keywords: M54; D23; D86; L23; K12; K13; 330; reputation free riding; collective punishment; formal and real responsibility